Public and Private: Two Views on a Same Project (2011)
Luz Miriam Muñoz, teacher at the school Benedicta Zur Nieden and María Teresa Correa, teacher at the school Compañía de María La Enseñanza, tell us about their experience as participants in Meeting Questions this year.